A comparison of the analgesic efficacy of vedaprofeno, carprofen or ketofen after ovariohysterectomy in bitches - Selmi,André Luis (2009)
In this study the authors aimed to compare the efficiency of carprofen, ketoprofen and vedaprofen for alleviating postoperative pain in bitches submitted to ovariohysterectomy (OH). Pre- and postoperative assessment of pain was made using serum levels of cortisol and glucose, the visual analogue scale (VAS) and the University of Melbourne pain scale (UMPS) in twenty-one bitches undergoing OH. Dogs were randomly assigned to one of three groups: vedaprofen at 0.5mg kg-1, carprofen at 2.2mg kg-1 or ketoprofen at 2.2mg kg-1. All analgesics were given orally 2 hour before surgery. Assessments were made before surgery and at 1, 2, 3, 4, 5, 6, 7, 8, 12 and 24 hours post-extubation. No dog of this study required additional doses of analgesics. There were no significant differences on serum cortisol and glucose concentrations among groups or from basal values, excepted one hour after extubation. No significant differences on pain scores were observed. It was concluded that vedaprofen provided as good a level of postoperative analgesia as carprofen and ketoprofen.